FETAL MACERATION IN A DOG - X, SOPHIA; C, JAYAKUMAR; ABHILASH; S, R; J, DEEPAK (The Indian Journal of Animal Reproduction, 2022)
A female dog crossed 61 days back with a history of brownish black vaginal discharge was confirmed of foetalmaceration based on radiographic and sonographic findings. Therapeutic management with a combination ofmifepristone and misoprostol failed to expel the foetus and a hysterotomy was performed to remove it. The dog hada successful conception in the subsequent estrus.
Keywords: Canine; Maceration; Medical management; Hysterotomy; Fertility